A Dipolar Cycloaddition Reaction To Access 6-Methyl-4,5,6,7-tetrahydro-1H-1,2,3triazolo4,5-cpyridines Enables the Discovery Synthesis and Preclinical Profiling of a P2X7 Antagonist Clinical Candidate - Chrovian, Christa C; Soyode-Johnson, Akinola; Peterson, Alexander A; Gelin, Christine F; Deng, Xiaohu; Dvorak, Curt A; Carruthers, Nicholas I; Lord, Brian; Fraser, Ian; Aluisio, Leah; Coe, Kevin J; Scott, Brian; et al. (Journal of medicinal chemistry, 2018)
A single pot dipolar cycloaddition reaction/Cope elimination sequence was developed to access novel 1,4,6,7-tetrahydro-5H-[1,2,3]triazolo[4,5-c]pyridine P2X7 antagonists that contain a synthetically challenging chiral center. The structure-activity relationships of the new compounds are described. Two of these compounds, (S)-(2-fluoro-3-(trifluoromethyl)phenyl)(1-(5-fluoropyrimidin-2-yl)-6-methyl-1,4,6,7-tetrahydro-5H-[1,2,3]triazolo[4,5-c]pyridin-5-yl)methanone (compound 29) and (S)-(3-fluoro-2-(trifluoromethyl)pyridin-4-yl)(1-(5-fluoropyrimidin-2-yl)-6-methyl-1,4,6,7-tetrahydro-5H-[1,2,3]triazolo[4,5-c]pyridin-5-yl)methanone (compound 35), were found to have robust P2X7 receptor occupancy at low doses in rat with ED50 values of 0.06 and 0.07 mg/kg, respectively. Compound 35 had notable solubility compared to 29 and showed good tolerability in preclinical species. Compound 35 was chosen as a clinical candidate for advancement into phase I clinical trials to assess safety and tolerability in healthy human subjects prior to the initiation of proof of concept studies for the treatment of mood disorders.A single pot dipolar cycloaddition reaction/Cope elimination sequence was developed to access novel 1,4,6,7-tetrahydro-5H-[1,2,3]triazolo[4,5-c]pyridine P2X7 antagonists that contain a synthetically challenging chiral center. The structure-activity relationships of the new compounds are described. Two of these compounds, (S)-(2-fluoro-3-(trifluoromethyl)phenyl)(1-(5-fluoropyrimidin-2-yl)-6-methyl-1,4,6,7-tetrahydro-5H-[1,2,3]triazolo[4,5-c]pyridin-5-yl)methanone (compound 29) and (S)-(3-fluoro-2-(trifluoromethyl)pyridin-4-yl)(1-(5-fluoropyrimidin-2-yl)-6-methyl-1,4,6,7-tetrahydro-5H-[1,2,3]triazolo[4,5-c]pyridin-5-yl)methanone (compound 35), were found to have robust P2X7 receptor occupancy at low doses in rat with ED50 values of 0.06 and 0.07 mg/kg, respectively. Compound 35 had notable solubility compared to 29 and showed good tolerability in preclinical species. Compound 35 was chosen as a clinical candidate for advancement into phase I clinical trials to assess safety and tolerability in healthy human subjects prior to the initiation of proof of concept studies for the treatment of mood disorders.